Maximality and Minimality in Comparatives - Meier, Cécile (Proceedings of Sinn und Bedeutung, 2019)
In this paper, I investigate more closely the contribution of modal operators to the semantics of comparatives and I show that there is no need for a maximality or minimality operator. Following Kratzer’s (1981, 1991) analysis of modal elements, I assume that the meaning of a modal sentence is dependent on a conversational background and an ordering source. For comparative environments, I demonstrate that the ordering source reduces a set of possible degrees to a single degree that is most (or least) wanted or expected, i.e., maximality and minimality readings of comparative constructions are an effect of the pragmatic meaning of the modal.